Medication guide for dose adjustment and management of cardiotoxicity and lipid metabolic adverse events of oral antineoplastic therapy - Ramos-Ruperez, Elena; Escudero-Vilaplana, Vicente; Ruiz-Briones, Paula; Collado-Borrell, Roberto; Villanueva-Bueno, Cristina; Revuelta-Herrero, José Luis; González-Haba, Eva; Garcia-Gonzalez, Xandra; Ibañez-Garcia, Sara; Perez-Ramirez, Sara; Zatarain-Nicolás, Eduardo; Herranz, Ana; et al. (Frontiers in Oncology, 2023)
Objective The management of cardiotoxicity concerning the use of oral antineoplastic agents (OAAs) is a challenge for healthcare professionals. Our objective was to create a comprehensive medication management guide with dose adjustment recommendations on OAAs concerning cardiotoxic and lipid metabolic adverse events (AEs) to assist healthcare professionals when prescribing OAAs. Materials and methods A review of the available information on all dose adjustments necessary to safely prescribe and dispense OAAs concerning cardiotoxicity was conducted. In January 2023, we identified all OAAs authorized by the European Medicines Agency (EMA). For each drug, the latest summary of product characteristics (SPC) approved by the EMA and the tertiary data source Lexicomp® were reviewed. Cardiotoxic AEs were recorded, namely, QT interval prolongation, decrease in left ventricular ejection fraction (LVEF), imbalances in blood pressure (hypertension and hypotension), alterations in heart rate (tachycardia and bradycardia), and thrombosis. Any available dose adjustment recommendations in case of an occurrence of these adverse events were collected. Results In all, 93 different OAAs had been approved by the EMA and were reviewed. Among them, 51.6% have recognized cardiotoxic AEs and 10.8% can cause alterations in lipid metabolism. A total of 27 (29.0%) OAAs had specific recommendations regarding QT prolongation; 88.9% were listed in the SPC and 59.3% in Lexicomp®. Eight OAAs (9.68%) have reported a decrease in LVEF, and four of these drugs, namely, encorafenib, lorlatinib, ripretinib, and sunitinib, have specific management recommendations. Almost half (49.5%) of currently approved OAAs can potentially alter blood pressure; 34 (36.6%) of them have been reported to cause hypertension and 12 (12.9%) are related to hypotension. Tachycardia and/or bradycardia are associated with 22.6% and 8.6% of the evaluated drugs, respectively. Regarding thrombosis, 30 (32.3%) of the drugs analyzed included the appearance of a thrombus as a possible AE. Conclusions More than half of the OAAs can produce cardiotoxic effects, with the most frequent being blood pressure alteration and QT interval prolongation with a non-depreciable incidence of LV dysfunction or thrombosis. Before starting the treatment, it is necessary to stratify baseline cardiovascular risk, plan a surveillance schedule, and consider referral to cardio-oncology units.